PHYSICS CONCEPTUAL UNDERSTANDING AND STUDENT RESPONSES TO GOOGLE SITES-BASED E-LKPD INTEGRATED WITH GUIDED INQUIRY - Ki'i, Oktavianus Ama; Mukin, Maria Ursula Jawa; Maing, Claudia Mariska Mardikawati; Sae, Yizrahya Juan (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
This study aims to examine students’ understanding of physics concepts and their responses to the use of Google Sites-based e-worksheets (e-LKPD) integrated with guided inquiry in physics learning at SMAN 3 Kupang. It was designed to address the demands of implementing the Merdeka Curriculum through innovative learning models, despite limited instructional time and learning facilities at school. This quantitative descriptive study with a one-shot case study design was conducted in an 11th-grade class and involved 25 students. The instruments were a multiple-choice test and a student response questionnaire, which were validated by 3 experts and obtained an I-CVI score of 1.00 (valid). The conceptual understanding test showed acceptable internal consistency reliability (KR-20 = 0.66), while the student response questionnaire showed excellent internal consistency reliability (Cronbach’s alpha = 0.93). The results showed that students’ understanding of physics concepts was in the high category, with a mean score of 82.8, while their responses to the use of e-LKPD were in the good category, with a mean score of 3.29. The highest response scores were found in guided inquiry activities, material clarity, and learning motivation. The novelty of this study lies in integrating guided inquiry stages into Google Sites-based e-LKPD as an innovative learning alternative in the context of limited instructional time, allowing students to manage the learning process more independently and thereby supporting their understanding of physics concepts. The results indicate that Google Sites-based e-LKPD integrated with guided inquiry can serve as a feasible digital learning medium in physics learning.